2017
DOI: 10.1111/cga.12205
|View full text |Cite
|
Sign up to set email alerts
|

Possible genes responsible for developmental delay observed in patients with rare 2q23q24 microdeletion syndrome: Literature review and description of an additional patient

Abstract: Cases of 2q23q24 microdeletion syndrome are rare. Patients with chromosomal deletions in this region often show language impairment and/or developmental delay of variable severity. Previous genotype-phenotype correlation study suggested GALNT13 and KCNJ3 as possible candidate genes for such phenotypes. We identified a new overlapping deletion in a patient with severe developmental delay. The identified deletion extended toward the distal 2q24.1 region, and more severe phenotypes in the present patient were con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 12 publications
1
8
0
Order By: Relevance
“…To our knowledge, this is the first time a point mutation leading to loss of function in NR4A2 is reported. Our patient's phenotype is similar to the previously described in individuals with de novo microdeletions encompassing NR4A2 at the 2q24.1 region and whose clinical manifestations were mainly characterized by language and cognitive delay . Our patient also presented focal motor seizures in the rolandic epilepsy spectrum, which expands the clinical manifestations related to NR4A2 haploinsufficiency and reinforces the predominance of language impairment associated with this condition.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…To our knowledge, this is the first time a point mutation leading to loss of function in NR4A2 is reported. Our patient's phenotype is similar to the previously described in individuals with de novo microdeletions encompassing NR4A2 at the 2q24.1 region and whose clinical manifestations were mainly characterized by language and cognitive delay . Our patient also presented focal motor seizures in the rolandic epilepsy spectrum, which expands the clinical manifestations related to NR4A2 haploinsufficiency and reinforces the predominance of language impairment associated with this condition.…”
Section: Discussionsupporting
confidence: 86%
“…Barge‐Schaapveld et al and Shimojima et al suggested previously that GPD2 haploinsufficiency was the most likely to be responsible for the 2q23q24 microdeletion phenotype. However, GPD2 probability of loss‐of‐function intolerance (pLi) is zero and over 100 loss‐of‐function variants are reported in ExAC,on the other hand, NR4A2 has a pLi = 1 and no loss‐of‐function variants in ExAC .…”
Section: Discussionmentioning
confidence: 98%
“…Among larger deletions, Leppa et al also reported 2 2q24.1 deletions (3.3 and 1.1 Mb) in patients with autism spectrum disorder (ASD), language delay and ID based on analysis of families from the Autism Genetic Resource Exchange project (AGRE) . Shimojima et al described a patient harboring a 4.5‐Mb 2q23.3q24.1 microdeletion with severe ID . These articles narrowed the critical region of overlap for ID, developmental delay (DD), ASD and language delay to NR4A2 and GPD2 genes .…”
Section: Introductionmentioning
confidence: 99%
“…5 Shimojima et al described a patient harboring a 4.5-Mb 2q23.3q24.1 microdeletion with severe ID. 6 These articles narrowed the critical region of overlap for ID, developmental delay (DD), ASD and language delay to NR4A2 and GPD2 genes. [4][5][6] Recently, Reuter et al reported the first patient with prominent language delay and mild cognitive impairment associated with a de novo deletion encompassing only NR4A2 gene.…”
mentioning
confidence: 99%
“…Exome sequencing could identify further additional variants associated with the phenotypes of the patient. Haploinsufficiency of a combination of genes in this region could lead to the developmental delay and dysmorphic facial appearance of the reported patients . Further analysis with animal models and a patient cohort could provide an insight to the underlying mechanism.…”
mentioning
confidence: 96%